2011
DOI: 10.1177/0731684411424630
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of unsaturated polyester/calcium carbonate nanocomposites

Abstract: In this study, the nano-sized calcium carbonate (CaCO 3 ) is synthesized using an in situ deposition technique and characterized using TEM. The particle size is found to be around 50-60 nm. Nanocomposites of UPR and nano-CaCO 3 particles are prepared by casting technique. The TEM study demonstrates that nano-CaCO 3 particles are dispersed in a UPR matrix uniformly and few agglomerations are found at and above 5 wt% of nano-CaCO 3 in the UPR matrix. XRD studies reveal the formation of nanocomposites. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…In order to improve those drawbacks, many attempts have been carried out, such as by incorporating fibers [11,12] and fillers [13,14] into the polymeric matrix. It has been reported that the addition of ceramic particles into polymer matrix has successfully enhanced the strength and hardness of the polymeric composites at room and elevated temperatures [1].…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve those drawbacks, many attempts have been carried out, such as by incorporating fibers [11,12] and fillers [13,14] into the polymeric matrix. It has been reported that the addition of ceramic particles into polymer matrix has successfully enhanced the strength and hardness of the polymeric composites at room and elevated temperatures [1].…”
Section: Introductionmentioning
confidence: 99%
“…The role of nanoparticles with various shapes and properties like CNTs, GO, clay, carbon black, nanoalumina, nano calcium carbonate and nano titanium on the performance of UP resins has been investigated. In all cases the optimum improvement in mechanical properties can be achieved by a fine dispersion of nanoparticles providing the maximum interfacial area.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the heat treatment produced an effective size reduction of the ZnO particles promoting an increase of the surface area. Hence, as the surface area/volume ratio increased with the decrease in the size of the nanoparticle, this might lead to the low stiffening effect [ 3 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…They are considered as heterogeneous catalysts and applied for acid–base and redox reactions. Furthermore, metal oxide nanoparticles are widely used in various reactions, which include oxidation, dehydration, dehydrogenation and isomerization, reasons they are versatile materials that can be used in applications such as medical technology, energy, water treatment and personal care products among others [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%